RESPON PUPUK SP-36 DAN PUPUK HAYATI PROVIBIO TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max) Merill L) Var. WILIS - victor panunggul (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2022)
The aim study was examine the response of SP-36 fertilizer and biofertilizer to the growth and yield of soybean (Glycine max) Merill L.) var. Willis. This study used a randomized block design (RAK). Faktor pemupukan SP-36 terdiri dari S0 = tanpa perlakuan (kontrol), S1 = 25 kg/ha, dan S2 = 50 kg/ha. Sedangkan faktor pupuk hayati terdiri dari D0 = (kontrol), D1 = 10 ml, dan D2 = 20 ml pupuk hayati. F-test to determine the level of significance in each treatment and the observed variable interactions using a significance level of 5%. If the effect is significant, the test is continued using Duncan's Multiple Range Test (DMRT) at a significance level of 5%. Data processing with DSAASTAT software. The results showed that the application of SP-36 fertilizer and biological fertilizer with a variable number of leaves with S2 treatment (50 kg/ha) was 33.02 strands while the best application of biological fertilizer was at 100 seeds, namely treatment D2 (20 ml) of 13.39 g. There was no interaction in the application of SP-36 fertilizer dose and biological fertilizer in each variable.